The Hyperreality of Female TikTok Users in Determining Criteria for Life Partners in Pamekasan - Khairul Umam (SOCIALE: International Journal of Social Studies, 2025)
The phenomenon of hyperreality occurs among young women in Pamekasan, particularly in determining the criteria for life partners. This study aims to delve deeper into the phenomenon currently unfolding and describe it in narrative form. Using a qualitative phenomenological approach, data were collected through interviews, observations, dan documentation, while analysis conducted using data reduction, data display, and conclusion drawing. Data validity is ensured through source triangulation techniques. Result reveal that Tiktok’s simulated representations of romantic relationship frequently adopt the five languages of love, thereby creating new expectations and standards regarding romantic relationships. These simulations significantly influence how young women in Pamekasan perspective on the reality of partnered life in the real world. Rather than relying solely on lived experiences, they compare their relationship with idealized potrayals om Tiktok, leading to shifts understanding of partner roles dan strategies for conflict resolution. Consequently, a boundary between real and simulated experiences becomes blurred, reinforcing hiperreality as a lens through which they evaluate relationship. This research highlights profound impact of digital content in shaping perseptions of romance, suggesting that social media not only reflect but also reconstruct cultural values surrounding intimacy and partnership.